2013
DOI: 10.1039/c3ra40932e
|View full text |Cite
|
Sign up to set email alerts
|

Iodo-BODIPY: a visible-light-driven, highly efficient and photostable metal-free organic photocatalyst

Abstract: Iodo-BODIPY: a visible-light-driven, highly efficient and photostable metal-free organic photocatalyst3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 48 publications
5
88
0
Order By: Relevance
“…BODIPY derivatives have recently emerged as one of the most prominent classes of organic dyes, with wide applications in fields such as fluorescent imaging and sensing, dye‐sensitized solar cells, lasing, non‐linear optics, photocatalysis, singlet oxygen generation and photodynamic therapy etc . These cis ‐constrained cyanines were first synthesized in 1968 (although the parent dye, 1 in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…BODIPY derivatives have recently emerged as one of the most prominent classes of organic dyes, with wide applications in fields such as fluorescent imaging and sensing, dye‐sensitized solar cells, lasing, non‐linear optics, photocatalysis, singlet oxygen generation and photodynamic therapy etc . These cis ‐constrained cyanines were first synthesized in 1968 (although the parent dye, 1 in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Singlet quantum yield studies revealed that HBDP,M eBDP,a nd PhBDP have negligible ability to generate 1 O 2 .D ramatic increases of 0.81, 0.64, and 0.83 for HBDP-2I, MeBDP-2I, and PhBDP-2I, respectively,w ere observeda fter the incorporation of two iodine atoms into the BODIPYm otifs (Table 11). [73] These enhancements could be attributed to ar edistribution of the electron cloud caused by the presence of iodine atoms, which was verified by theoretical studies on the frontier molecular orbitalsb ased on ground-state structures.…”
Section: Carbon-sulfur Bond Cleavagementioning
confidence: 66%
“…However, it is difficult to stop the overoxidation of phenol with TiO 2 because the oxidation power of the hole produced by photoirradiation of TiO 2 is too strong to be controlled . In contrast to inorganic photocatalysts, metal‐free organic photocatalysts, the oxidation power of the excited state of which can be finely controlled, have been utilized as selective oxidation of substrates …”
Section: Photochemical Hydroxylation Of Benzene With Watermentioning
confidence: 99%